Measurement technology and intelligent instruments IX : selected papers of the 9th International Symposium on Measurement Technology and Intelligent Instruments (ISMTII-2009), June 29-July 2, 2009, Saint-Petersburg, Russia - Chugui, Yuri V. (Trans Tech Publications, 2010)
This special collection focuses on measurement science and metrology: micro- and nano- measurements; novel measurement methods and diagnostic technologies, including non-destructive and dimensional inspection, optical and X-ray tomography and interferometry, terahertz technologies for science, industry and biomedicine, intelligent measuring instruments and systems for industry and transport, measurements of geometrical and mechanical quantities, measurements and metrology for humanitarian fields and education in measurement science. The aim was to present the current state and evolution of measuring technology and intelligent instruments, to highlight novel technologies for science, industry and engineering, and to spot promising ways towards further development, of new technologies for measurement, at the international level.
Keywords: Engineering instruments -- Congresses.; Measuring instruments -- Congresses.; elektronické knihy; electronic books